On an elliptic system of p(x)-Kirchhoff-type under neumann boundary condition - Yucedag, Zehra; Avci, Mustafa; Mashiyev, Rabil (Mathematical Modelling and Analysis, 2012)
In the present paper, by using the direct variational method and the Ekeland variational principle, we study the existence of solutions for an elliptic system of p(x)-Kirchhoff-type under Neumann boundary condition and show the existence of a weak solution.